Cultivation of medicinal and aromatic plants in India – way forward - Janakiram, T; Reddy, R Nagaraja; Manivel, P (Indian Horticulture, 2019)
Medicinal and Aromatic Plants (MAPs) are an integral part of human welfare since time immemorial and evolved as science along with human evolution. The MAPs play an important role in ensuring health and income security worldwide. They have been used for the treatment of various human diseases and aliments due to their unique properties. Demand for the medicinal plantbased drugs are increasing day-by-day due to their availability and safety. India is rich in medicinal and aromatic plants diversity. The ICAR and Council of Scientific and Industrial Research (CSIR) are two apex research organizations engaged in MAP research in our country. The research priorities are biodiversity conservation, breeding and cultivar development, cultivation, quality management, diseases and pest management, biotechnology, post-harvest management and mechanization, marketing and knowledge management for sustainable development of MAP sector, says Dr T Janakiram, ADG (Hort) at the ICAR Headquarters, New Delhi.